Metal-Organic Frameworks - Zafar, Fahmina; Sharmin, Eram (IntechOpen, 2016)
The emerging and interesting field of MOF encouraged us to bring forth the book titled ''Metal Organic Frameworks''. The book is divided into three sections. Section A consists of introduction, Section B comprises the synthesis and characterization techniques, and Section C is dedicated to the applications of MOFs. The book would be useful for scientists and researchers interested in the field of MOFs.